A theoretical study on the strain energy of helicene-containing carbon nanobelts. Issue 95 (16th November 2020) - Watanabe, Kosuke; Segawa, Yasutomo; Itami, Kenichiro
Abstract : In this study, the theoretical analysis of the strain energy of helicene-containing carbon nanobelts is reported. Abstract : In this study, the theoretical analysis of the strain energy of helicene-containing carbon nanobelts is reported. It was found that the combined method of linear regression analysis and suitable homodesmotic reactions can successfully estimate the strain energies of various helicene-containing carbon nanobelts including previously synthesized chiral (18, 12) carbon nanobelts.